Respuesta :

Answer: g(x)=(9x+1)

Step by step explanation:

The function 2x + 3 is equivalent to g(x) + f(x) if the g(x) = (9x + 1) and f(x) = (-7x + 2)

What is a function?

It is defined as a special type of relationship, and they have a predefined domain and range according to the function every value in the domain is related to exactly one value in the range.

We have a function:

h(x) = (3x - 4)

f(x) = (-7x + 2)

g(x) = (9x + 1)

Find h(x) + g(x):

= (3x - 4) + (9x + 1)

= 12x -3

Find g(x) + f(x):

= (9x + 1) + (-7x + 2)

= 2x + 3

Thus, the function 2x + 3 is equivalent to g(x) + f(x) if the g(x) = (9x + 1) and f(x) = (-7x + 2)

Learn more about the function here:

brainly.com/question/5245372

#SPJ2

ACCESS MORE